Characterization of enzymatic coagulation of milk from Holstein cows - Beux, Simone; Aparecido de Lima, Vanderlei; Léa Meira Silveira, Joana; Luisa Cerri, Maria; Fogagnoli Simas, Fernanda; Cassandro, Martino; Nogueira, Alessandro; Waszczynskyj, Nina; Alberti, Aline (Seven Editora, 2023)
The milk coagulation capacity of fourteen Holstein cows was analyzed in three different periods of the year, using a low amplitude dynamic oscillatory rheological analysis. In most of the samples analyzed, the modules G’ and G" increased with the time of coagulation and the gels were characterized as weak. However, the rheological results in real-time of the coagulation showed that the milk of two animals, one for presenting slow coagulation (greater than 36 minutes) and the other for not coagulating are unsuitable for cheese production by enzymatic coagulation. The values ​​of the Temperature and Humidity Index were less than 72 and did not influence the rheological properties. Significant differences between fat and lactose contents and between pH and somatic cell score values were found between the analysis periods. Evaluating the milk coagulation capacity and the strength of the gel formed are essential to assess the appropriate destination of milk, that is, milk for cheese production or milk for the production of derivatives that do not depend on enzymatic coagulation. DOI: https://doi.org/10.56238/tfisdwv1-012